Selective Serotonin Reuptake Inhibitors and Fertility: Considerations for Couples Trying to Conceive. Issue 2 (March 2019) - Sylvester, Christie; Menke, Marie; Gopalan, Priya
Abstract : Background: Depression and anxiety are prevalent disorders and are often treated with selective serotonin reuptake inhibitors (SSRIs). Infertility is also common among couples, and rates of depression and anxiety are elevated in this population, but the impact of SSRIs on fertility has received modest attention. This review explores the literature available on SSRIs, fertility, and infertility-treatment outcomes to assist clinicians in better counseling their patients. Methods: A literature search was performed using the search terms infertility, fertility, antidepressants, and SSRIs to identify studies that investigated the relationship between SSRI use and fertility or infertility-treatment outcomes. Results: Twenty relevant articles were identified, 16 of which were original research studies. The studies varied in design, quality, and outcome measures, limiting meta-analysis. The prevalence of antidepressant use ranged from 3.5%–10% in reproductive-age women, with infertile populations reporting less use. The two studies examining the impact of SSRIs in fertile women had conflicting results. Six of the seven studies in infertility patients found no significant association between SSRIs and treatment outcomes; three observed a trend, however, toward reduced fecundability or negatively influenced fertility biomarkers. One study found treatment increased pregnancy rates. In males, most studies were of relatively poor quality, though six of the seven studies found SSRIs to have an adverse effect on semen parameters. Conclusions: There is insufficient evidence at present to propose that SSRIs reduce fertility or influence infertility-treatment outcomes. SSRIs may have an adverse impact on sperm quality, but further research is warranted.